Delayed presentation of food protein-induced enterocolitis syndrome (FPIES) to okra in a toddler - Hunter Hall; Sara Anvari; Fallon Schultz; Olubukola Ojuola; Nicholas L. Rider (Allergy, Asthma & Clinical Immunology, 2024)
Abstract Background Food protein-induced enterocolitis syndrome (FPIES) is a non-immunoglobulin E (IgE) -mediated food allergy predominantly observed in infants and characterized by the delayed onset of vomiting following ingestion of a trigger food. An increase in research and clinical consideration of FPIES has led to the discovery of unique deviations from the standard FPIES triggers and presentations. Case presentation A 34-month-old female patient with a history of consuming okra daily presented to medical attention after developing classic FPIES symptoms to okra beginning at 14-months of age. Conclusions Recently, awareness about the varied nature of FPIES clinical presentation has come to light. This case is the first to describe FPIES to the fruit okra that developed over a 12-month time span after previously tolerating the food. This case serves to emphasize the importance of understanding the range of FPIES symptoms to improve recognition and expedite best practice recommendations.